Type I photosensitizers based on phosphindole oxide for photodynamic therapy: apoptosis and autophagy induced by endoplasmic reticulum stress. Issue 13 (2nd March 2020) - Zhuang, Zeyan; Dai, Jun; Yu, Maoxing; Li, Jianqing; Shen, Pingchuan; Hu, Rong; Lou, Xiaoding; Zhao, Zujin; Tang, Ben Zhong
Abstract : Phosphindole oxide-based photosensitizers with Type I reactive oxygen species generation ability are developed and used for endoplasmic reticulum stress-mediated photodynamic therapy of tumors. Abstract : Photodynamic therapy (PDT) is considered a pioneering and effective modality for cancer treatment, but it is still facing challenges of hypoxic tumors. Recently, Type I PDT, as an effective strategy to address this issue, has drawn considerable attention. Few reports are available on the capability for Type I reactive oxygen species (ROS) generation of purely organic photosensitizers (PSs). Herein, we report two new Type I PSs, α -TPA-PIO and β -TPA-PIO, from phosphindole oxide-based isomers with efficient Type I ROS generation abilities. A detailed study on photophysical and photochemical mechanisms is conducted to shed light on the molecular design of PSs based on the Type I mechanism. The in vitro results demonstrate that these two PSs can selectively accumulate in a neutral lipid region, particularly in the endoplasmic reticulum (ER), of cells and efficiently induce ER-stress mediated apoptosis and autophagy in PDT. In vivo models indicate that β -TPA-PIO successfully achieves remarkable tumor ablation. The ROS-based ER stress triggered by β -TPA-PIO-mediated PDT has high potential as a precursor of the immunostimulatory effect for immunotherapy. This work presents a comprehensive protocol for Type I-based purely organic PSs and highlights the significance of considering the working mechanism in the design of PSs for the optimization of cancer treatment protocols.